ANALISIS FAKTOR PENGULANGAN RADIOGRAF (REPEAT ) DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM DAERAH PADANG PARIAMAN - mareta, santa (Jurnal Kesehatan Medika Saintika, 2024)
On increasing efficiency in producing good radiograph results without wasting material, and time for diagnostic imaging. One of the methods that will be described is repeat analysis which aims to determine the percentage of repetition of radiographs that occur and the causes of repetition of radiographs in the Radiology Installation at RSUD. Padang Pariaman which has an impact on the radiation dose received by patients. Descriptive quantitative research design, conducted directly by observation on Computed Radiography and conventional examination patient register books. The results showed that the repetition rate of radiographs in October to December 2022 at the Radiology Installation of the Padang Pariaman Regional General Hospital was 3.1%. The factor that occurs the most repetition is the equipment factor with a repetition of 22 times with a percentage of 45.83% this repetition occurs because the image that has been exposed when scanned becomes white or there is no image of the object. The percentage of radiograph repetition rates that occur in the Radiology Installation of Padang Pariaman Hospital exceeds the standard tolerance limit set by the Indonesian Minister of Health Number 129 / Menkes / SK / II / 2008 which is ≤ 2%.Key words: Radiology, Repeat, Computed Radiography